I-V characteristics and impedance spectroscopy of a single grain boundary in Nb-doped SrTiO3 - Kim, SH; Kim, HT; Park, JH; Kim, Y (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
The I-V character and impedance of a single grain boundary in No-doped SrTiO3 were investigated. The specimens were sintered at 1570 degrees C in air. A microelectrode method was used to measure the I-V character and the impedance of a single grain-to-grain junction. The single grain boundary of Nb-doped SrTiO3 was shown to have non-ohmic behavior, and the breakdown voltage of a single grain boundary was found to be about 7 V. The precise value of impedance could be determined by the microelectrode method. From fitting results, it was shown that the capacitances of the grain boundary increased and the resistances of the grain boundary decreased with increasing Nb content. (C) 1999 Elsevier Science Ltd.
Keywords: LAYER CAPACITORS; ZNO VARISTOR; CERAMICS